Teacher-Learner Relationship and Academic Learning: A Correlational Study - Arnado, Axl Rose; Barsobia, Elryn Llydz; Galbizo, Charisse; Maboot, Cyankine John; Soylon, John Edward (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between teacher-learner relationship and academic learning among Senior High School students of Holy Cross of Mintal, Inc. in Davao City. It was grounded in Self-Determination Theory, Bruner’s Constructivist Theory, and Vygotsky’s Sociocultural Theory, which collectively emphasize the role of relatedness, scaffolding, and social interaction in promoting student learning. Using a quantitative descriptive-correlational design, the study gathered data from 121 respondents selected through stratified equal allocation sampling from 11 Senior High School sections. Data were collected through adapted and modified survey instruments with reliability scores above 0.85, measuring teacher support, teacher communication, academic performance, and learning engagement. Mean, standard deviation, and Pearson product-moment correlation were used to analyze the data. Findings revealed a high level of teacher-learner relationship and a high level of academic learning among the respondents. Teacher communication obtained the highest mean among the relational indicators, while academic performance slightly exceeded learning engagement among the academic indicators. The study also found a significant moderate positive correlation between teacher-learner relationship and academic learning, with teacher support showing a stronger relationship with academic learning than teacher communication. These results indicate that positive interpersonal bonds between teachers and learners contribute meaningfully to student engagement and academic performance. The study concludes that academic learning is not only cognitive but also socially mediated through supportive and communicative classroom relationships. It recommends that learners strengthen rapport with teachers, that teachers provide relational scaffolding and encouragement, and that school leaders integrate relational pedagogy into supervision and professional development. The study aligns with SDG 4: Quality Education by supporting inclusive, effective, and meaningful learning environments. Its sustainability impact lies in strengthening educational and institutional sustainability through improved teaching practices, student support systems, and long-term learner development.